Perodua Myvi engine fuel consumption map and fuel economy vehicle simulation on the drive cycles based on Malaysian roads - Ramdan, Muhammad Iftishah (EDP Sciences, 2017)
This paper presents the fuel consumption engine map for a 1.3L Perodua Myvi passenger car. The engine dynamometer and the engine throttle are controlled, to create the operating conditions for the engine map. Interpolation work is done in MATLAB, to create a 3D fuel consumption engine map. The engine map is used in a fuel-economy estimation simulation, using the city and the highway drive cycles based on Malaysian roads. The fuel economy values generated from the simulations are similar to experimental fuel consumption results.